Dirt eaudiobook - Woods, Stuart (Stone Barrington, 1996)
Welcome to the world of Dirt, where a celebrity's carefully-crafted image, decades in the making, can be destroyed by a single indiscretion and the snap of a shutter. Fast-paced, lively and swirling with action, Dirt is best-selling author Stuart Woods' latest novel featuring one of his most popular characters, New York detective Stone Barrington. Amanda Dart is the queen of the glitzy, trashy gossip world until rivals publish an underground scandal sheet called Dirt. When Dart's and her associates' peccadilloes are faxed to news desks across the nation, the motive becomes clear: blackmail. In desperation, Dart and her publisher call Barrington for help. Can Barrington find the culprits before the payoff, or will the gossip community come up with its own, deadlier solution? Fascinating and irresistible as only good gossip can be, this sensational look at the steamy, cutthroat world of gossip columns and tabloid journalism is Stuart Woods at his best.